2017
DOI: 10.1111/php.12758
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen Inhibits UVB‐induced Basal Cell and Squamous Cell Carcinoma Development in Ptch1+/−/SKH‐1 Hairless Mice

Abstract: Naproxen possesses anti-proliferative and pro-apoptotic effects besides its known anti-inflammatory functions. Here, we demonstrate the anti-cancer effects of naproxen against UVB-induced BCCs and SCCs in a highly susceptible murine model of UVB carcinogenesis. Naproxen significantly inhibited UVB-induced BCCs and SCCs in this model. Tumor number and volume were significantly decreased (p<0.005 and p<0.05, respectively). Inhibition in UVB-induced SCCs and BCCs was 77% and 86%, respectively, which was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Experimentally, a rodent diet containing a selective Cox-2 inhibitor had suppressive effects on BCC formation in Ptch1 +/− mice 49 . Similarly, treatment with an NSAID, naproxen, significantly suppressed UV-induced BCC and SCC formation 50 . The role of Cox-2 in skin tumor formation was also supported by transgenic Cox-2 overexpression 51 .…”
Section: The Role Of Cox-2 In Stem Cell-originating Cutaneous Tumor Fmentioning
confidence: 94%
“…Experimentally, a rodent diet containing a selective Cox-2 inhibitor had suppressive effects on BCC formation in Ptch1 +/− mice 49 . Similarly, treatment with an NSAID, naproxen, significantly suppressed UV-induced BCC and SCC formation 50 . The role of Cox-2 in skin tumor formation was also supported by transgenic Cox-2 overexpression 51 .…”
Section: The Role Of Cox-2 In Stem Cell-originating Cutaneous Tumor Fmentioning
confidence: 94%
“…Decreased levels of cyclooxygenase-(COX-) 2, NF-κB. and inducible nitric oxide synthase (iNOS) were identified [86].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%
“…Tumors from treated animals had lower invasiveness with increased E-cadherin expression and reduced expression of EMT markers (e.g., N-cadherin, vimentin, Snail, Twist). In BCC and SCC cells, it was shown that naproxen reduced UVB-induced skin carcinogenesis through reducing endoplasmic reticulum (ER) stress pathways (49).…”
Section: Non-melanoma Tumors: Squamous Cell and Basal Cell Skin Carcimentioning
confidence: 99%
“…The effects were associated with decreased PCNA and cyclin D1 expression, increased apoptosis and inflammation-related molecules (e.g., iNOS, COX-2 and nuclear NF-κBp65). Even remaining tumors after naproxen therapy displayed a lower aggressive potential, lower EMT marker expression (e.g., N-cadherin, vimentin, Snail and Twist) and enhanced E-cadherin expression (49).…”
Section: Non-melanoma Tumors: Squamous Cell and Basal Cell Skin Carcimentioning
confidence: 99%